The Changes and Characteristics of the Exchange of Chinese and Japanese Food Culture—From the Perspective of the Acceptance of Japanese Food Culture - Zhang, Yayi (Cultural and religious studies, 2020)
This paper investigates the characteristics and evolution process of Sino-Japanese diet culture exchange in each historical period, analyzes the possible impact of globalization on Sino-Japanese diet culture exchange, and discusses the development direction of innovative mode of Sino-Japanese diet culture exchange under the background of globalization.